2012
DOI: 10.1055/s-0031-1295790
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characteristics of the human hepatic stellate cell line LX–2

Abstract: The human hepatic cell line LX-2 has been described as tool to study mechanisms of hepatic fibrogenesis and the testing of antifibrotic compounds. It was originally generated by immortalisation with the Simian Vacuolating Virus 40 (SV40) transforming (T) antigen and subsequent propagation in low serum conditions. Although this immortalized line is used in an increasing number of studies, detailed genetic characterisation has been lacking. We here have performed genetic characterisation of the LX-2 cell line an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The spontaneously immortalized human HSC cell line LX‐2 (provided by Dr. Robert G Bennett, University of Nebraska, with the permission of Dr. Scott Friedman, Icahn School of Medicine at Mount Sinai, New York, NY, USA) (25) was authenticated by American Type Culture Collection (Manassas, VA, USA) using short tandem repeat analysis and matched to the published short tandem repeat loci of LX‐2 (26). Cells were seeded in 6‐well plates in DMEM (Corning, Corning, NY, USA) supplemented with 2% fetal bovine serum (Atlanta Biologicals, Flowery Branch, GA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The spontaneously immortalized human HSC cell line LX‐2 (provided by Dr. Robert G Bennett, University of Nebraska, with the permission of Dr. Scott Friedman, Icahn School of Medicine at Mount Sinai, New York, NY, USA) (25) was authenticated by American Type Culture Collection (Manassas, VA, USA) using short tandem repeat analysis and matched to the published short tandem repeat loci of LX‐2 (26). Cells were seeded in 6‐well plates in DMEM (Corning, Corning, NY, USA) supplemented with 2% fetal bovine serum (Atlanta Biologicals, Flowery Branch, GA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The authors further found that the transient overexpression of SHP or the incubation with AICAR or metformin diminished the HCV‐associated activation of NF‐κB as well as the production of TGF‐β and connective tissue growth factor (CTGF/CCN2), again demonstrating the antifibrotic potential of SHP. Moreover, the overexpression of SHP and activation of AMPK ameliorated HSC invasion in a co‐culture system with the genetically well‐characterized immortalized human hepatic stellate cell line LX‐2 .…”
mentioning
confidence: 99%